Supplementary Material for: Associations of 4-year trajectories in anthropometric and DXA-measured obesity indicators with all-cause and cardiovascular mortality in older Chinese adults - figshare admin karger (2628495) (2025)
Background: Given the scarce evidence on mortality risks associated with obesity trajectories beyond body mass index (BMI), this study examined the independent associations of changes in anthropometric and DXA-measured indicators of general and abdominal obesity with all-cause and cardiovascular mortality in older Chinese adults. Methods: 1495 male and 1506 female participants, with a mean age of 71.75 years and BMI at 23.75 kg/m2 at baseline in 2001-2003, were followed up on mortality till mid-2020. BMI, waist-to-hip ratio (WHR), and DXA-measured indicators including whole body fat mass (WBFM) and android-to-gynoid ratio (AGR) were assessed at baseline and year 4. Sex-specific multivariable Cox proportional hazards regression and competing-risk survival model were employed. Results: A substantial 4-year decline (>10%) in obesity indicators, except WHR, was associated with elevated mortality risks. General obesity indicators, particularly BMI, remained as strong predictors after accounting for abdominal obesity measures. The association of BMI with all-cause mortality was largely attributable to change in whole body muscle mass (WBMM) in men and to both changes in WBFM and WBMM in women, whereas their roles in cardiovascular mortality were less apparent. Despite elevated mortality associated with increases in general obesity measures, lower all-cause mortality was found for increase in AGR in men. Conclusion: Notwithstanding critiques on BMI for obesity assessment, BMI change appears to be a robust indicator of survival in older Chinese adults, as it reflects not only fat mass but also lean muscle mass changes. Moreover, increases in abdominal obesity indicators do not seem to pose mortality risks.